Istikṣāf adawāt al-Tamāsuk al-Nahwi wa al-mu’jamī bii’tibārihā buniyah ‘ala insijam al-Nusūs liāyāti al-Tasāmuh al-Dīnī (dirōsatu tahlīli al- Khithōbi fi al-Qur’āni al-Karīmi) - Afif Kholisun Nashoih; Syamfa Agny Anggara; Moh. Ubaidillah; Muhammad Ichsan (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
The Qur'an is quite different from most general texts. Among the most prominent differences is that it is said that the Qur’an includes elements of the discourse structure that lead to the harmony and unity of the texts. Therefore, this simple article is written with the aim of describing the textual harmony of the verses of religious tolerance in the Holy Qur’an - which are spread in 7 chapters - by applying the theory of discourse analysis promoted by Halliday & Hasan. In particular, this research aims to explore cohesion tools, whether grammatical or lexical. To achieve these desired goals, the researchers used observations followed by note-taking techniques to collect data. In conducting data analysis, the